Genotype of Staphylococcus aureus Isolated from Otorrhea of Chronic Otitis Media. (23rd August 2013) - Komori, Masahiro; Kobayashi, Taisuke; Hyodo, Masamitsu
Abstract : Objectives: Staphylococcus aureus (SA) causes about 50% of cases of chronic otitis media (COM). Specific characteristics of a geographical region and diseases such as impetigo and atopic dermatitis were identified as factors in the molecular epidemiology of SA. We compared the genotype of SA isolated from otorrhea of patients with COM with the genotype isolated from the nasal inhabitants of healthy subjects. Methods: Forty SA isolates, including 11 methicillin‐resistant SA (MRSA) isolates, were collected from patients with COM who underwent tympanoplasty between April 2009 and July 2012. Multilocus sequence typing was performed on these isolates. First, PCR and DNA sequencing were performed on seven housekeeping genes of SA. A clonal complex (CC) was defined as the coincidence of a gene among five of the seven genes. In patients with MRSA, the period until the ears became dry postoperatively was investigated. Results: The proportion of CC8 and CC5 SA strains of COM were greater than that of nasal inhabitants, possibly because the CCs included MRSA stains. The proportion of CC188 and CC508 SA strains, which are major strains in nasal inhabitants, was smaller. The proportion of CC121, CC509, and CC59 SA strains, which are minor strains in nasal inhabitants, was greater. The periods were 207 days for the CC8 MRSA strain (n=4), 189 days for the CC5 MRSA strain (n = 4), and 95 days for the CC 95 MRSA strain (n=1); no significant difference was found. Conclusions: This study revealed discrepancies in CCs between SA from COM and SA from nasal inhabitants.